Evaluation of efficacy of pregabalin as premedication for post-operative analgesia in open appendicectomy - Bijapur, Mubina Begum; Kudligi, Nazeer Ahmed; Moizuddin, Syed; Rasool, Mohammed; K., Shabeer Ali (International Journal of Research in Medical Sciences, 2023)
Background: Pregabalin is gamma amino butyric acid (GABA) structural analogue, effectively used in management of different neuropathic pain, incisional and inflammatory injuries. Current study aimed to evaluate the efficacy of pregabalin 75 mg with a placebo as premedication for post-operative analgesia in patients posted for open Appendicectomy under regional anesthesia. Methods: A randomized controlled trial was conducted on 90 patients undergoing open Appendicectomy under regional anesthesia. The patients were divided in two groups of 45 each: group C (placebo); group P (75 mg pregabalin), drug was administered orally 60 minutes before surgery. The Ramsay sedation scale (RSS) was used for assessment of sedation and the visual analog scale (VAS) was used to determine pain at rest and cough, along with assessment of time required for rescue analgesics on the first post-operative day. Results: The RSS scores were significantly higher in groups P as compared to the controls (p<0.001). Postoperative VAS scores for pain both at rest and on cough were significantly reduced in group P (p<0.001). Rescue analgesic consumption decreased significantly in group P (p<0.001). The time at which first dose of rescue analgesia administered was 4.50±3.04 hours in group C, 10.90±5.37 hours in group P (p<0.001). Conclusions: Pregabalin as premedication prolong the postoperative analgesia in addition to decreased consumption of analgesics.